ANALYSIS OF THE AUDIENCE'S MEANING MAKING PROCESS TOWARDS THE MOVIE DISNEY CARTOON MULAN (1998) AND DISNEY LIVE ACTION MULAN (2020) - Krisnawan, Gabriella Joselyn; Ridwan, Nia Amelia; Meyrasyawati, Dewi; Afdholy, Nadya (E-Journal of Cultural Studies, 2024)
This article explores the portrayal of Mulan as a symbol of women's empowerment in Disney’s animated "Mulan" (1998) and live-action adaptation (2020). Drawing on Stuart Hall’s theory of reception study, the study examines how both films depict Mulan’s defiance of traditional gender roles and her journey towards empowerment. Through qualitative analysis of audience responses, it reveals that respondents from diverse backgrounds perceive Mulan as a bold, intelligent, and resourceful heroine who challenges societal expectations. In the 1998 animated film, Mulan's valor in replacing her father in battle resonates with themes of courage and sacrifice, while the 2020 live-action adaptation emphasizes her personal growth and mastery of chi, focusing less on romance and more on self-actualization. The findings underscore the films’ success in conveying messages of female empowerment across cultural and cinematic contexts, reflecting shifts in societal attitudes and interpretations of gender roles. Keywords : Mulan, Disney, Reception, Audience Meaning, Societal Expectations,   Gender Roles